Advancing the modified face name associative memory exam in cognitive aging research: insights into connectomic correlates and task reliability - Liu, Yilin; Sundman, Mark H.; Hinderaker, Dalen; Yu-Chin Chen, Allison; Green, Jacob M.; Haaheim, Lisbeth G.; Siu, Hannah M.; Jezerc, Catherine; Lai, Kaitlyn; Chen, Carol; Guss, Parker; Chou, Ying-hui (Frontiers in Aging Neuroscience, 2025)
IntroductionThe shift toward earlier detection in the Alzheimer's disease (AD) continuum underscores the need for more sensitive cognitive outcome assessments (COAs). Traditional COAs may lack precision in capturing cognitive dysfunction during preclinical stages. The Face-Name Associative Memory Exam (FNAME), a cross-modal task that integrates verbal and non-verbal memory, offers enhanced sensitivity and has shown associations with amyloid-β burden across the AD continuum, even in asymptomatic older adults.MethodsThis manuscript reports on two experiments, broadening insights into this promising COA. Experiment 1 (descriptive observational, repeated-measures design) (N = 85) evaluates the alternate form reliability of a modified FNAME (mFNAME) by serially administering eight distinct versions of the task, revealing good reliability for mFNAME metrics and the absence of significant practice effects. Experiment 2 (cross-sectional observational design) (N = 32) examines structural and functional network topology to investigate neural correlates of mFNAME performance in non-demented older adults.ResultsExperiment 1 demonstrated good alternate form reliability with no significant practice effect. Experiment 2 revealed significant associations between mFNAME performance and network properties like global efficiency, local efficiency, and system segregation in the default mode network (DMN) and medial temporal network (MTN). Subsequent analyses into more granular elements of the MTN and DMN revealed latent variables accounting for up to 44% of the covariance in mFNAME performance.DiscussionsThese findings deepen the understanding of the FNAME's psychometric properties and the neural correlates underlying task performance, providing insights into its utility as a sensitive COA early in the continuum of AD and related dementias.